Effect of soybean oil/PODE/ethanol blends on combustion and emissions on a heavy-duty diesel engine. (15th March 2021) - Zhang, Zhao; Liu, Xin; Liu, Haifeng; Wu, Yangyi; Zaman, M; Geng, Zhenlong; Jin, Chao; Zheng, Zunqing; Yue, Zongyu; Yao, Mingfa
Highlights: Effects of soybean oil-PODE-ethanol blended fuels on diesel engine are investigated. PHRR of D100 is higher than two soybean oil blended fuels. BTE of D100 is the highest in the same CA50 and combustion duration. Soot emissions of S70P30 are the lowest with the same CA50 and combustion duration. The weighted BSFC of D100 is the lowest in the WHSC test cycle of Euro VI. Abstract: In this study, an experimental study has been conducted to explore the effects of soybean oil/PODE/ethanol blends on the combustion and emission characteristics in a diesel engine. Three tested fuels are 70% soybean oil/30% PODE by volume denoted as S70P30, 70% soybean oil/15% PODE/15% ethanol by volume denoted as S70P15E15 and baseline pure diesel denoted as D100. The impacts of CA50 and combustion duration at engine speed of 1415 rpm and 1.15 MPa BMEP are investigated. As the CA50 delays, BTE and NOx emissions decrease and soot emissions increase; as the combustion duration prolongs, BTE increases first and then decreases, NOx emissions decrease and soot emissions increase. CA50 has more significant effect on BTE, NOx and soot emissions than combustion duration. At the same CA50 and combustion duration, the trend in BTE and soot emissions is D100 > S70P15E15 > S70P30; for NOx emissions the trend is S70P30 > S70P15E15 > D100. For example, When CA50 is 17 °CA ATDC and the combustion duration is 25 °CA, the BTE of D100, S70P15E15 and S70P30 are 41.0%, 39.1% and 38.6%, respectively; the NOx emissions are approximately 6.4 g/kW·h, 7.0 g/kW·h and 7.8 g/kW·h, respectively; the soot emissions are 0.004 g/kW·h, 0.0011 g/kW·h and 0.0008 g/kW·h, respectively. Finally, the WHSC test cycle of Euro VI regulation is performed. Comparing two soybean oil blended fuels, S70P15E15 and S70P30 are similar in soot emissions, but S70P15E15 is lower in NOx emissions and weighted BSFC.